Attitude of Kerala Youth towards Tourists - E. Murali (Commerce Spectrum, 2014)
ourism is a curious phenomenon both for tourists and hosts. In tourism, the attitude, concern, participation and sense of responsibility of host matters a lot in creating a favorable environment. If people have a positive attitude towards tourism and tourists, this encourages them to be conscious of preserving the tourism resources of the country. Therefore, it is essential to shape a positive attitude among the host people towards tourism/tourists. The youth population in the host community has more responsibility in this regard for developing sustainable tourism in a destination. This paper analyses the attitude of youth community towards tourists visiting Kerala with descriptive and inferential statistical tools. The results of the study disclose that, irrespective of their gender and residential location, youth are found to be having the attitude of welcoming the presence of tourists in their area. In respect of mentality of providing helps to tourists also youth are found to be having a positive attitude.